Harnessing Plasticity in an Amine‐Borane as a Piezoelectric and Pyroelectric Flexible Film. (19th March 2020) - Zhang, Yan; Hopkins, Margaret A.; Liptrot, David J.; Khanbareh, Hamideh; Groen, Pim; Zhou, Xuefan; Zhang, Dou; Bao, Yinxiang; Zhou, Kechao; Bowen, Chris R.; Carbery, David R.
Abstract: We demonstrate that trimethylamine borane can exhibit desirable piezoelectric and pyroelectric properties. The material was shown to be able operate as a flexible film for both thermal sensing, thermal energy conversion and mechanical sensing with high open circuit voltages (>10 V). A piezoelectric coefficient of d 33 ≈10–16 pC N −1, and pyroelectric coefficient of p ≈25.8 μC m −2  K −1 were achieved after poling, with high pyroelectric figure of merits for sensing and harvesting, along with a relative permittivity of ϵ 33 σ ≈ 6.3. Abstract : Pyroelektrisches Boran : Plastizität und mechanische Flexibilität von Trimethylaminboran wurden genutzt, um einen piezo‐ und pyroelektrischen Film herzustellen, der für Sensor‐ und Energieanwendungen geeignet ist.